ANALYSIS OF MONITORING AND FULFILLMENT OF CREDIT OBLIGATIONS IN COMMERCIAL BANKS - Mansurjon Mardonakulovich, Bustonov; Bahromjon Ibroximovich, Rakhimov (International Journal of Business, Law, and Education, 2021)
Monitoring of investment projects is carried out not only in the process of its implementation, but also during the period of their financing. The importance of pre-project monitoring is that it is better and more important than monitoring during project financing. As a result, it will allow investors to better meet their project implementation goals. Pre-project monitoring will include: Searching for investment concepts; initial project preparation; Final formation of the project and its feasibility study; Permanent review of the project and making decisions on it. Going through these stages will ensure investment. In order to create such a situation, all aspects of the implementation of the investment idea must be carefully prepared and a business plan (investment project) developed accordingly. Such a project is in the best interest of potential investors, which means that the results of the research have yielded the desired results. A useful calculation of the results and analysis will allow you to make a decision (step by step) on choosing the best option (scheme) for project implementation and financing. The benefits of this phase approach are evident in demonstrating and increasing the cost of project preparation. This phase also enables the identification and selection of the most promising and effective projects, which will ensure the timely detection and rejection of unsuccessful projects and the prevention of large-scale wastage. This sort of projects is always important. Finding and selecting business ideas appropriate to investing is an important starting point for investing activities. This can eventually become the basis for mobilizing investment funds. For this purpose the initial preparation of the project must be carefully done. The task of the initial project preparation phase is to develop a suitable business plan for an investment project, that is, to address a common issue for any commercial activity. The mission of such a business plan is based on finding answers to two key questions: How interesting is the concept of an investment project and is it logical to continue to work on it and to prepare valid data to evaluate the feasibility and financial viability of the project? Are there any research and conceptual aspects that are important to the future success of this investment project? At the final stage of the project's development and evaluation of its technical and economic and financial advantages, the feasibility study and analysis of the project should provide an alternate consideration of options and problems related to all aspects of the investment. Preparation of all types of information for final decision making is the core content of the final stage of the project and a thorough assessment of the financial advantage of the project. This step should only be possible if the required financial resources are sufficiently secure. The final and next step is the final review of the project and the final decision on the feasibility of financing the project, which provides for the evaluation that is the basis for the decision-making process of the project.